Labor Market Shocks, Parental Beliefs, and Children's Socio-Emotional Development - Maria Josefina Baez; Gianna Claudia Giannelli; Lucia Mangiavacchi (Institute of Labor Economics (IZA), 2025)
This paper investigates how shifts in local labor markets influence maternal expectations about future support from their children, and how those expectations affect adolescents' socio-emotional development. Using panel data from the Young Lives study in Peru (Rounds 4 and 5), the analysis exploits exogenous variation in female employment opportunities across departments through a shift-share instrument. Results show that improvements in women's local labor demand reduce the likelihood that mothers expect emotional or financial support from their children in adulthood. These lower expectations are, in turn, associated with improved socio-emotional development among adolescents, captured through standardized indices of self-esteem, self-efficacy, peer relations, and pride. The findings suggest that economic expansion may relax intergenerational expectations of support, thereby reducing the psychological burdens placed on children. This study contributes to research on gendered labor shocks, parental beliefs, and the socio-emotional consequences of intergenerational dynamics, particularly in low- and middle-income countries, showing how economic change can influence child development through shifts in maternal expectations.
Keywords: D1; J1; I2; 330; shift share; maternal expectations; socio-emotional skills; Peru